Effectiveness of Rational Emotive Behavior Therapy (REBT) Group Format Therapy to Improve Student Self Concepts. - Riza Novilda; Yeni Karneli; Yarmis Syukur (Universitas Negeri Padang, 2019)
This research is motivated by (1) students prefer to have friends with certain people, (2) students who are smart but lack courage in expressing opinions, (3) students who are diligent in joining extracurricular activities but are less courageous in opinion. This study aims to examine the effectiveness of the Rational Emotive Behavior Therapy (REBT) group format in an effort to improve students' self-concepts caused by irrational thinking. This study uses the Quasi Experiment method with the design of The Non Equivalent Control Group. The subjects of the study were eighth grade students of SMP Negeri 3 Lubuk Basung (10 control groups and 10 experimental groups). The research instrument used a self-concept scale with a validity of 0.387 and a reliability of 0.870. Data analysis using nonparametric statistics with Wilcoxon Signed Rank Test and Kolmogorov Smirnov 2 Independent Samples. The findings of the study show that the REBT approach to the effective group format to improve students' self-concepts, this can be seen from the increase in the self-concept scores of the experimental group students is greater than the control group's self-concept scores.